The Effect of Removable Partial Denture and Salivary Changes during Pregnancy (Mustansiria Dental Journal, 2018)
The calcium, inorganic – phosphate of 20 pregnant women with age (20 – 45)years wearing removable partial denture divided into 3 trimester and 10 womenmarried non pregnant as control.In resting saliva the concentration of calcium not changed significantly in pregnantwomen, and inorganic – phosphorus found not to be changed significantly.The aim of this study was to see the pregnancy related change in human saliva andrelation to the oral findings and effect of wearing removable partial denture.